The Other Side of Sustainability: Contradictions and Risks in Contemporary Green Innovations - Monaco, Salvatore (Sustainability, 2025)
Drawing on a comparative qualitative analysis of case studies in reforestation, urban greening, and green mobility—from both the Global North and the Global South—this paper aims to identify recurring critical patterns associated with eco-blind initiatives, in order to uncover the most significant contradictions and risks underlying contemporary green innovation strategies. Eco-blindness occurs when interventions, although genuinely aimed at promoting sustainability, generate negative consequences by prioritizing environmental goals while overlooking the socio-cultural and territorial contexts within which they are embedded. Among the most significant patterns identified are the top-down imposition of sustainability frameworks, the exclusion of local actors from decision-making processes, the commodification of environmental goods, and the symbolic displacement of communities. In response to these challenges, the analysis emphasizes the transformative potential of place-based and participatory approaches, particularly when sustainability initiatives are co-designed with local communities and tailored to the specificities of territories. The paper concludes by reflecting on the potential contributions of social research in fostering more holistic, equitable, and territorially grounded models of environmental governance.